(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT The digital revolution that we are experiencing today is one of the most prominent manifestations of scientific development that has occurred in human history. After the development in digital payment methods, or what is called digital money, the most prominent development witnessed by the digital revolution is at the level of monetary operations, as encrypted virtual currencies are considered a contemporary economic disaster, and there has been a lot of talk about them and their effects and provisions, due to the spread of dealing with them in various places in the world, especially... The Hazm currency has recently appeared in a number of Arab countries. To answer an emerging question, how can a completely new issue such as the Hazm currency be studied? From which other questions arise: What are the economic standards for cash? Did Islam specify a specific form of criticism? Can digital money be considered cash from an economic perspective? How do we understand the position of Islamic jurisprudence on digital money? I began to search for the nature of this currency, and after research and study, I learned about this new currency, its nature, and the corresponding money that jurists have spoken about in the past and in recent times and clarified a ruling. I explained the extent of the risks facing this currency, and the extent of its effects on the economy and people, and then I explained the position of jurisprudence. The Islamic Bank has decided to deal with it, and has reached the following conclusions: What is related to it in terms of its monetary value is that it has not achieved the economic functions of currency efficiently, and as for its issuance, the state should not allow it. Due to the great extent of its economic risks, the state must control it and issue laws to subject it to it because it poses a great danger to the state’s general economy. Finally: I recommended that the state, if necessary, deal in digital currencies; A digital currency issued by official bodies subject to the laws and legislation of the state’s economic institution.